Managing sustainability—Does the integration of environmental, social and governance key performance indicators in the internal management systems contribute to companies' environmental, social and governance performance? - Maria Gebhardt; Toni W. Thun; Marcel Seefloth; Henning Zülch (Business Strategy and the Environment, 2022)
Assessing whether a company is sustainable or not is challenging for investors. For this reason, it is particularly important how companies integrate and manage sustainability. This paper primarily aims to investigate the effects of implementing environmental, social and governance (ESG) key performance indicators (KPIs) in the internal management system (IMS) on ESG performance. Further, the effect of a consistent use of ESG KPIs in the IMS and the management compensation scheme (MCS) on ESG performance is examined. Using hand-collected data of the largest German-listed companies, this study employs t tests for differences in means and ordinary least square (OLS) regressions to study these associations. The results indicate that the implementation of ESG KPIs in the IMS increases ESG performance. In addition, the performance for environmental and social sub-dimensions is enhanced. No significant influence of a consistent use of ESG KPIs in the IMS and the MCS on ESG performance is observed. The results highlight that implementing ESG KPIs in the IMS is a practical approach to manage sustainability and to increase ESG performance. Our findings have practical and theoretical implications for researchers, regulators and companies considering the integration of sustainability and further communicating transparently and strengthening investor trust.
Keywords: 330; ESG KPIs; ESG performance; internal management system; management compensation scheme; sustainability management